DESAIN PESAN KAMPANYE MEDIA SOSIAL INSTAGRAM @DITJEN.DIKTI (Studi Kasus: Program Kampus Merdeka Direktorat Jenderal Pendidikan Tinggi Riset dan Teknologi Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi RI) - Ramel Maulynda Rachma (2023)
The Instagram account of the Directorate General of Higher Education, @ditjen.dikti, received 1 negative comment, 3 positive comments, and 11 comments unrelated to the content of the Kampus Merdeka logo that was uploaded on September 15, 2020. This raises concerns about how a government institution conveys its campaign message. One of the key units within the Indonesian Ministry of Education and Culture (Kemendikbud RI) that uses Instagram to promote the Kampus Merdeka program aims to reach its primary targets, namely students, lecturers, industry stakeholders, and universities. This research aims to explain how the campaign message design of Kampus Merdeka, conducted by the Directorate General of Higher Education, is based on the ethos, pathos, and logos aspects of Aristotle's Rhetoric theory and how the content structure of the Kampus Merdeka program campaign on the @ditjen.dikti Instagram account is created. This study employs a qualitative approach with a case study method and field research type. Data collection is conducted through in-depth interviews with research subjects, including informants and key informants. The results of the research indicate that the design of the Kampus Merdeka program campaign message lacks strong elements of ethos, pathos, and logos because the messages conveyed are primarily informative. The pathos aspect is weak in the 29 content slides examined as it relies mainly on visual elements. Ethos is present in the 29 content slides through the logo and images of figures included. However, only 8 out of 29 content slides examined have logos elements. The structure of the Kampus Merdeka program campaign message is one-sided because the uploaded content is promotional in nature. The presentation format uses a carousel content format with a title followed by content, and there are 2 pieces of content in which conclusions are written in the captions.